Beyond Modern Management: The Barokah Model as a Spiritual Approach to Islamic Educational Innovation - Nur Zazin; Salman Basri; Satria Tama (Al-Qalam Institute, 2025)
This study aims to formulate and analyze the Barokah Management model as a spirituality-based approach to driving innovation in Islamic educational institutions. Educational innovation has become a critical issue amid global competition, particularly for private Islamic institutions, which face financial constraints and limited resources compared to the public sector. These challenges necessitate a contextually grounded management model that integrates modern quality standards with spiritual values to ensure sustainability and competitiveness. This research employs a qualitative biographical design that focuses on the leadership of KH. Sulaiman Nain at the Foundation. Data were collected through in-depth interviews, documentation, and field observations, and analyzed using an interactive model with triangulation for validity. The findings reveal that institutional expansion is driven by mission-oriented innovation rooted in religious values. The Barokah Management model integrates POAC functions with spiritual principles, generating “metaphysical efficiency” in resource-limited contexts. Organizational culture reflects high loyalty, resilience, and a sense of transcendent accountability among staff. Spiritual leadership fosters a low-cost, high-trust governance system that enhances institutional performance. These findings demonstrate that spiritual capital can substitute for material limitations and sustain innovation. This study presents a novel theoretical framework and recommends further research using comparative and mixed-methods approaches.